Survival Status, Length of Stay, and Predictors of Mortality Among Neonates Admitted in the Neonatal Intensive Care Unit of Gurage Zone Public Hospitals - Bogale Chekole MSc; Tamene Fetene Terefe MSc; Shegaw Geze Tenaw MSc; Bitew Tefera Zewudie MSc; Fisha Alebel GebreEyesus MSc; Amare Kassaw MSc; Belete Gelaw Walle MSc; Agerie Aynalem Mewahegn MSc; Betelihem Tadesse MSc; Yibeltal Mesfin MSc; Muche Argaw MSc; Haimanot Abebe MSc; et al. (SAGE Publishing, 2023)
Background Many countries need to accelerate their progress to achieve the sustainable development goal target of neonatal death. It is still high in Ethiopia. Thus, this study aimed to assess the mortality predictors and length of hospital stay among Neonates admitted to the Neonatal Intensive Care Unit of Gurage zone public Hospitals. Method In this study, a facility-based retrospective follow-up study was applied among 375 neonates admitted to the NICU of selected public hospitals in the Gurage zone from June 1, 2019 to June 30, 2021. The researchers used Epi-Data entry 3.1 for the data entry and then exported it to STATA version 14 for analysis. The Kaplan-Meier survival curve and log-rank test were used to estimate and compare the survival time of categorical variables, respectively. Result The researchers observed about 85 (22.7% with 95%CI: 18.7, 27.2) deaths from the 2305 person-days follow-up. The median survival time was 14 days. The overall incidence density rate was 36.9 per 1000 person-days observed (95%CI: 29.8, 45.6). Perinatal asphyxia (AHR: 2.9[CI: 1.8; 4.8]), cesarean section as a mode of delivery (AHR: 1.1[CI; 1.01; 1.15]), maternal age of greater or equal to 35 years (AHR: 1.1[95% CI: 1.01, 1.15]), and twin pregnancy (AHR: 2.3[95% CI: 1.2, 4.3]) were predictors of neonatal mortality. Conclusion The survival rate of neonates was higher compared to other studies. So, to reduce the burden of neonatal mortality, health care providers should give special attention to twin pregnancies, neonates delivered via cesarean section, and neonates with a problem of perinatal asphyxia.